Maturation and Reproduction of African Catfish in Recirculated System in Uzbekistan Environments - N.E. Djumanova; G.U. Urunova; F.Zh. Utemuratova; B.A. Mamatkulova (Zien Journals, 2023)
Mature females and males of African catfish (Clarias gariepinus) were overwintered, artificial reproduction using gonadotropic injections was carried out, eggs were incubated, larvae were reared from January to mid-April 2022 in closed conditions of a recirculated aquaculture system with a water temperature of 18-25 ° C. In April, fingerlings were transplanted into cages in the Tuyabuguz reservoir. By the end of October, catfish reached a body weight of 1.1 - 3.4 kg.
Keywords: Aquaculture; African catfish; Сlarias gariepinus; artificial fish reproduction